Use of Google Sites Improves Islamic Religious Education Learning Outcomes - majid, tajuddin; Musdalifah Muhammadun; Zulfah (IAIN Parepare, 2024)
This research discusses the use of Google Sites in improving Islamic Religious Education learning outcomes in class XI at SMAN 6 Barru . This type of research uses a Quasi Experimental Design model with the form of Pretest-Posttest Control Group Design which was carried out in Barru. The main instrument of this research is a test supported by research instruments with data collection in the form of documentation, with a research sample of 21 people divided into 2 classes, namely a sample of 10 people as the control class and 11 people as the experimental class. The sampling technique used was purposive sampling . The results of this research show that what improves student learning outcomes in using Google Sites is making it easier for students in the teaching and learning process in the classroom and outside the classroom, including the following: (1) accessibility of learning materials , (2) interactivity and collaboration, (3) personalization of learning, and (4) increasing student motivation and involvement in the teaching and learning process. The learning outcomes of Class -average (mean) is 72.27 in the experimental class while 68 in the control class. Based on the results of the Paired Sample T-Test, a significance value of 0.000 is obtained, which means sig, 0.05, so H o is rejected and H a accepted. It can be concluded that there are differences in student learning outcomes before and after using Google Sites in Islamic Religious Education learning .